PENERAPAN MODEL STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) BERBANTUAN MEDIA BAAMBOOZLE TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA - Fadilah, Dila; Sundayana, Rostina; Sri Sumartini , Tina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The purpose of this study was to determine how the Student Teams Achievement Divisions (STAD) learning model with the help of Baamboozle media affects students' ability to communicate mathematically about the material of sets. The method used was a quasi-experimental study with a quantitative approach, and a non-comparable control group design was used. All eighth-grade students at MTs Darussalam in Garut Regency, West Java, were the subjects of this study. The research sample consisted of two classes, class VIII-B served as the experimental class, and class VIII-A served as the control class. In total, 52 students were selected using a purposive sampling method. A mathematical communication ability test was used as a research instrument and the data were analyzed with descriptive and inferential statistics. The data did not have a normal distribution, according to the results of the normality test, so the Mann-Whitney U test was used. According to the results of the study, the experimental class had an average N-Gain of 0.66 greater than the control class of 0.30, and the significance value of the Mann-Whitney U test was less than 0.05, indicating a significant difference between the two classes. In addition, students achieved 80.77% learning mastery in the experimental class. These results indicate that the Baamboozle-assisted STAD learning model improves students' mathematical communication skills better than direct learning.